2016
DOI: 10.1109/tgrs.2015.2499379
|View full text |Cite
|
Sign up to set email alerts
|

Water Depth Inversion From a Single SPOT-5 Dataset

Abstract: International audienceKnowing bathymetry at intermediate depth, over large areas, and at a reasonable cost is a key issue. Spaceborne remote sensing techniques must play an essential role in retrieving such bathymetry. In this paper, a method is proposed that aims to address this issue without any in situ measurements by exploiting the characteristics of the SPOT-5 satellite dataset. The proposed method is designed to provide bathymetry from two optical SPOT-5 satellite images separated by a time lag DT of 2.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 21 publications
1
30
0
Order By: Relevance
“…The present example is based on the study described by [98]. The preliminary work of [99] has shown that it is possible to determine wave celerity directly from optical satellite imagery from the SPOT-5 sensor, thanks to the technical characteristics of the SPOT-5 satellite.…”
Section: Correlation-wavelet-bathymetry (Cwb) Methods (Multi-spectral)mentioning
confidence: 99%
See 1 more Smart Citation
“…The present example is based on the study described by [98]. The preliminary work of [99] has shown that it is possible to determine wave celerity directly from optical satellite imagery from the SPOT-5 sensor, thanks to the technical characteristics of the SPOT-5 satellite.…”
Section: Correlation-wavelet-bathymetry (Cwb) Methods (Multi-spectral)mentioning
confidence: 99%
“…The bathymetry: (a) measured; and (b) stimated by the CWB (in m) method on the area of Saint Pierre on Reunion Island. The isobaths represented in black range from 0 to 50 m depth with a step of 5 m (from[98]). …”
mentioning
confidence: 99%
“…Although constant efforts by the research community have been made toward either simple or complex paradigms of coastal evolution (e.g, static retreat by Bruun, 1962;Hanson et al 2010), the coastal response to perpetually changing ocean forcing conditions is still unclear (Cooper and Pilkey, 2004;Ranasinghe et al 2016). Recently, several methods using satellite imagery have been proven reliable (Poupardin et al 2016;Bergsma et al 2019;Raucoules et al 2019) in estimating large-sale coastal bathymetry at unprecedented resolution. One prominent approach is the use of multispectral imagery in estimating shallow bathymetry, until 20 m depth approximately in the case of clear waters.…”
Section: Coastal Bathymetrymentioning
confidence: 99%
“…Among these methods, some use external data (measurements or offshore modeling), while others directly extract the wavelength and wave celerity informations from the satellite images. Despite their high potential, these methods were only applied to a limited spatial domain (Danilo and Melgani, 2016;Poupardin et al 2016) using basic wave physics (none uses the information contained in the full spectrum in an optimal way), and can still be improved. Having access to high-resolution coastal bathymetry is one major prerequisite in order to reduce uncertainty in the estimation of wave contribution to coastal sea level changes (e.g.…”
Section: Coastal Bathymetrymentioning
confidence: 99%
“…-A high spatio-temporal resolution continuous marine-land topography and bathymetry database, with height precision better than 20 cm is needed. However, lower resolution datasets such as those that can be produced with Sentinel 2 or other data may still be useful for understanding coastal evolution (e.g., Poupardin et al, 2016).…”
Section: Discussionmentioning
confidence: 99%